Prospek Thorium pada Endapan Aluvial di Daerah Koba dan Sekitarnya - Ngadenin, Ngadenin; Indrastomo, Frederikus Dian; Widodo, Widodo (EKSPLORIUM, 2012)
The objective of the present study of the thorium in placer of Koba, Central Bangka District, Bangka Belitung Province and its surrounding is to find out thorium prospect in alluvial deposits. The study method are geological and radiometrical mapping, grain counting and thorium grade analysis of pan concentrated. Result of the research reveals that lithology of the investigation area compose of metasandstone unit with radiometric value of 35 c/s - 200 c/s, granite intrusion with radiometric value of 140-550 c/s and alluvial with radiometric value of 40-300 c/s SPP2NF. Content of monazite in the pan concentrated is approximately 7.54 %, content of thorium in pan concentrated of 1410 ppm, covered alluvial deposits of about 400 kilometers square with average thickness 3.77 meters. According to the study thorium prospect in Koba area is feasible to be Based on the type of deposit (placer) which are relatively easy to be mined at low cost, high content of monazite and thorium so that the prospect thorium Koba feasible to develop.